Bale Mediation As A Dispute Settlement Institution Outside The Court (Study On Bale Mediation, East Lombok Regency, West Nusa Tenggara) - Muh. Arief Syahroni; Arief Rachman Hakim; Frans Simangunsong (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The Supreme Court as the executor of judicial power has made various efforts to prevent these problems, including by increasing the number of justices from academics and other legal practitioners besides career judges, revamping the organization internally, empowering the oversight function to enforcing one roof for all matters. financial, organizational and administrative under the Supreme Court itself, but these efforts have not yet shown significant results. This condition certainly cannot be allowed to occur because it can trigger vigilante actions and can cause chaos in society. The solution to this problem is to develop alternative dispute resolution outside the court through non-formal channels, one of which is through mediation. Bale Mediasi is an institution that facilitates dispute resolution outside of court based on local wisdom, so that it can resolve various legal issues faced by the community without having to end up in court. The establishment of this institution is a form of government acknowledgment in providing protection, respect and empowerment for the existence of local wisdom through customary institutions in carrying out mediation functions, preventing and reducing conflicts or disputes in the community earlier, and holding dispute resolution in the community through mediation in order to create peaceful, orderly and harmonious atmosphere.